A Large-Scale Systematic Study of Palaeoeskimo Soapstone Vessel Fragments from Newfoundland and Labrador - Erwin, John C. (ARCTIC, 2016)
The examination of Palaeoeskimo soapstone vessel fragments from the Province of Newfoundland and Labrador provides a better understanding of the use and significance of this technology. While researchers have tacitly accepted the function of soapstone vessels and their use by these populations on the basis of ethnographic analogy, no large-scale systematic study of these vessels has ever been produced to test these assumptions in this region. Results of this study, which are based upon the measurement of more than 3600 soapstone vessel fragments, demonstrate ways in which vessel function may be determined from both morphological characteristics and carbonization patterns. It is also concluded that there are recognizable stylistic differences between vessels used in Labrador and those used on the Island of Newfoundland. The methods employed in this study may be useful in the examination of similar vessels elsewhere in the Arctic. L’examen de fragments de récipients en stéatite du Paléoesquimau en provenance de la province de Terre-Neuve-et-Labrador permet de mieux comprendre l’utilisation de cette technologie et son importance. Bien que les chercheurs aient tacitement accepté la fonction des récipients en stéatite et leur utilisation par ces populations en s’appuyant sur une analogie ethnographique, aucune étude systématique d’envergure n’a jamais été réalisée à l’égard de ces récipients pour valider ces hypothèses dans cette région. Les résultats de cette étude, comportant la mesure de plus de 3 600 fragments de récipients en stéatite, montrent comment la fonction des récipients peut être déterminée tant à partir des caractéristiques morphologiques que des marques de carbonisation. L’étude permet également de conclure qu’il existe des différences stylistiques reconnaissables entre les récipients employés au Labrador et ceux utilisés sur l’île de Terre-Neuve. Les méthodes employées dans le cadre de cette étude pourraient aider à examiner des récipients semblables, ailleurs dans l’Arctique.